2013
DOI: 10.1002/app.39578
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a chitosan ligand for the removal of copper from aqueous media

Abstract: A novel chitosan derivative, 8‐hydroxyquinioline‐2‐carboxaldehydechitosan (CSHQ) Schiff base, was synthesized by a simple condensation process. The structure of the resulting product was confirmed by Fourier transform infrared spectroscopy, solid‐state 13C‐NMR, differential scanning calorimetry, scanning electron microscopy, and energy‐dispersive X‐ray spectroscopy. Further, the synthesized CSHQ Schiff base was used as an adsorbent for the removal of Cu(II) from aqueous solution. The adsorption of Cu(II) onto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 64 publications
2
18
0
2
Order By: Relevance
“…This indicated that the Langmuir condition was the ideal one for the adsorption mechanism. 57 The results of the Redlich−Peterson isotherm also supported the suitability of the Langmuir model.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 64%
“…This indicated that the Langmuir condition was the ideal one for the adsorption mechanism. 57 The results of the Redlich−Peterson isotherm also supported the suitability of the Langmuir model.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 64%
“…1C shows the FTIR spectra of CS 8 (a), low molecular weight chitosan pyruvic acid derivative (b) and cross-linked low molecular weight chitosan pyruvic acid derivative (c). The most important bands for the low molecular weight chitosan (CS 8 ) can be ascribed as follows: 3340 cm −1 ( OH and NH 2 group stretching vibrations), 2930 cm −1 ( CH stretch in CH as well as CH 2 ), 1593 cm −1 (NH 2 bending vibration), 1404 cm −1 ( CH symmetric bending vibrations in CHOH ), 1074 cm −1 ( CO stretch in COH ) (Reddy & Lee, 2013). Subsequent to the modification of low molecular weight chitosan with pyruvic acid, a new band belonging to COOH at 1734 cm −1 was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The pH of solution is one of the important parameters since it influences the surface charge and dissociation of the functional groups on the adsorbents. pH also alters the degree of ionization and speciation of the metal ions (Reddy and Lee 2013). The normal pH of the sludge was found to be 8.5.…”
Section: Effect Of Adsorbent Dosagementioning
confidence: 98%